Mineralogy and Morphology of Roasted Copper Concentrates Produced in Simulated Suspension Smelting Conditions - Ari JokiIaakso (The Minerals, Metals and Materials Society, 1989)
Three different sulphidic raw materials were treated in a laboratory scale laminar flow fur-nace simulating suspension smelting conditions. The materials were a pure chalcopyrite concentrate, a high-antimony concentrate (tetrahedritic), and crushed copper mattes. The gas preheating temperatures were 500 -1 100°C ana the atmospheres ranged from N2 to N2 -75 % O2, Two particle size fractions were used for the concentrates with x = 20 -38 um and x = 62 -74 um, and three for the granulated copper mattes with x < 37 um, x = 62 -88 um, and x = 125 -177 um. Scanning electron microscopy combined with energy dispersive analysis and backscattered electron analysis was used for determining the morphology and the mineralogy of the reacted particles. Fragmentation of the particles were observed in all materials during the flash oxidation, the conditions depending on the iron and sulphur content and the original particle size fraction of the material. The melting and/or reaction stages of the particles in different conditions were studied from powder samples. Polished sections were examined in order to follow the development of porosity and the mineralogy of the particles.